1999
DOI: 10.1093/heapol/14.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Health for Some? The Effects of User Fees in the Volta Region of Ghana

Abstract: This paper reports key findings and conclusions from a 1996 study of user fees and exemptions in the Volta Region of Ghana. A variety of data sources and methods were used, including interviews with patients and managers, community-based focus group discussions, analysis of facility records and analyses of previous household survey data. Official fee levels and exemption categories were established in 1985. While this legislation made provision for drug fees to be 'at cost' and thus to be revised in line with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(107 citation statements)
references
References 8 publications
3
102
1
1
Order By: Relevance
“…There is extensive literature on the impact of user fees in low-to-middle income countries, 1,[3][4][5][19][20][21][22] and the subject of their removal, particularly in Africa, is now a heavily debated issue. The findings of the various studies reported in this paper show that in contexts where poverty is widespread, user fees represent a major obstacle to the use of essential health services and exacerbate impoverishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is extensive literature on the impact of user fees in low-to-middle income countries, 1,[3][4][5][19][20][21][22] and the subject of their removal, particularly in Africa, is now a heavily debated issue. The findings of the various studies reported in this paper show that in contexts where poverty is widespread, user fees represent a major obstacle to the use of essential health services and exacerbate impoverishment.…”
Section: Discussionmentioning
confidence: 99%
“…They add to the evidence that financial barriers associated with user fees contribute significantly to low utilisation of health services. [20][21][22][23][24][25] Under-use of health services is strongly associated with high mortality rates when one considers that a substantial number of deaths are preventable through access to effective health interventions. [26][27][28][29][30] health centres are among other barriers to healthcare access in resource-poor contexts, 26,31,32 some of which were reported in the current surveys.…”
Section: Discussionmentioning
confidence: 99%
“…This, according to Nyonator and Kutzin, (1999) was essentially a revolving drug fund that was introduced nationwide in 1992. The fee per drug item charged to users was related to the procurement cost of the item, marked-up with fixed percentages by central and regional medical stores.…”
Section: Introductionmentioning
confidence: 99%
“…7 A study costing maternal health care in one district in 1999 found cost recovery rates of between 152% for deliveries and 211% for caesareans in mission hospitals, but did not shed light on affordability relative to women's income. 10 Problems such as under-funding of exemptions from user fees in general have also been found, [11][12][13] which have meant that exemptions are available in theory but not always in practice if the provider is not reimbursed for lost income.…”
Section: Introductionmentioning
confidence: 99%